2013
DOI: 10.4055/cios.2013.5.3.188
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Femoral Tunnel Positioning Using 3-Dimensional Computed Tomography and Radiographs after Single Bundle Anterior Cruciate Ligament Reconstruction with Modified Transtibial Technique

Abstract: BackgroundThe purpose of this study is to report a modified transtibial technique to approach the center of anatomical femoral footprint in anterior cruciate ligament (ACL) reconstruction and to investigate the accurate femoral tunnel position with 3-dimensional computed tomography (3D-CT) and radiography after reconstruction.MethodsFrom December 2010 to October 2011, we evaluated 98 patients who underwent primary ACL reconstruction using a modified transtibial technique to approach the center of anatomical fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 21 publications
(26 reference statements)
1
30
0
Order By: Relevance
“…All reconstructions were performed with a modified transtibial technique using a quadruple hamstring tendon autograft. 12) Through the anteromedial portal, a microfracture awl was placed just behind the bifurcate ridge to make the center of the anatomical femoral tunnel. The triangular, funnel-shaped bony trough was employed to slip the eccentrically positioned guide into the anticipated anatomic center, which is part of the modified transtibial technique.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All reconstructions were performed with a modified transtibial technique using a quadruple hamstring tendon autograft. 12) Through the anteromedial portal, a microfracture awl was placed just behind the bifurcate ridge to make the center of the anatomical femoral tunnel. The triangular, funnel-shaped bony trough was employed to slip the eccentrically positioned guide into the anticipated anatomic center, which is part of the modified transtibial technique.…”
Section: Methodsmentioning
confidence: 99%
“…The triangular, funnel-shaped bony trough was employed to slip the eccentrically positioned guide into the anticipated anatomic center, which is part of the modified transtibial technique. 12) An ACL guide (Linvatec, Largo, FL, USA) was used to make the tibial tunnel at an angle of 47.5°, and the tunnel was positioned in the center of the remnant ACL stump. The tibial tunnel was made to have the same thickness as the graft using an expansion reamer.…”
Section: Methodsmentioning
confidence: 99%
“…4-6 A more oblique graft resulting from a more horizontal femoral tunnel in the coronal plane was found to better resist rotational forces than a more vertical femoral tunnel. [7][8][9] However, increased coronal obliquity correlated with a more circular aperture of the femoral tunnel, 10 differing in shape from its normal oval anatomic footprint. The biomechanical superiority of increased coronal graft obliquity of the femoral tunnel has increased interest in independent femoral drilling techniques of ACL reconstruction, such as anteromedial (AM) portal and outside-in (OI) techniques, which are independent of tibial drilling during ACL reconstruction.…”
mentioning
confidence: 91%
“…Unlike previous reports that state that femoral tunnels produced from traditional transtibial techniques tend to lie more proximal and anterior than the anatomic position, our modified transtibial technique can produce a femoral tunnel that is only slightly distal and posterior to the anatomic position with the funnel-shaped bone trough. 2,8,9 A recent study on 3-dimensional computed tomography evaluation after anatomic ACL reconstruction with the modified transtibial technique reported that the mean value of the femoral tunnels was between the AM and posterolateral bundle position compared with the mean 3. (A) The guide pin tends to be placed more distally and anteriorly than the anatomic center of the femoral footprint as viewed from the anterolateral portal in the left knee that is kept in flexion.…”
Section: Discussionmentioning
confidence: 99%
“…MODIFIED TRANSTIBIAL TECHNIQUE e229 value from multiple measurements of the anatomic ACL footprints in cadaveric knees from previous studies. 8 Another important factor to consider when producing an anatomic femoral tunnel during the transtibial ACL reconstruction technique is the starting point of the tibial tunnel. Recent studies have attempted to achieve anatomic femoral attachment sites by altering the starting point of the tibia bone tunnel.…”
Section: Discussionmentioning
confidence: 99%